A CONSTRUÇÃO DE USINAS NOS CURSOS D’ÁGUA NA FRANÇA PÓS-REVOLUCIONÁRIA:: REFLEXÕES SOBRE O TRATADO DO DOMÍNIO PÚBLICO DE JEAN-BAPTISTE PROUDHON - de Sant’Anna Alves Primo, Marcelo (Prometheus - Journal of Philosophy., 2020)
Between the late eighteenth and early nineteenth centuries, a new legal trend began to distinguish between the public domain and the private domain of public persons. At the same time, there is a need to establish precise criteria that would make it possible to clearly distinguish both assets, given the important consequences for assets, and including them in one of these categories. The most important systematization of this new trend is due to Jean-Baptiste Víctor Proudhon, with his Treaty of the public domain or the distinction of the goods considered mainly in relation to the public domain (1833). In the light of the author's theses, we will reflect in particular on some chapters of his Treaty when he comments on the construction of power plants in post-revolutionary France.